Integrasi literasi digital dalam pembelajaran menulis paragraf argumentasi di kelas IV - Agnesti Bilqis; Dinn Wahyudin; Effy Mulyasari (COLLASE (Creative of Learning Students Elementary Education), 2026)
This study aims to describe the implementation of digital literacy in Indonesian language learning through argumentative paragraph writing in elementary school students. The research was conducted with fourth-grade students using a descriptive qualitative approach. Data were collected through student worksheets involving topic selection. Searching for information online, and composing paragraphs based on personal opinions. The results show that students were able to independently access digital information and use it to support their arguments in writing. This activity encouraged students to think critically, express their opinions, and construct simple argumentative texts. Integrating digital literacy into Indonesian language learning has proven to provide a more meaningful and relevant learning experience in line with current developments.